202. Implementation and Three-Year Results of Antimicrobial Stewardship Program in a Three Hospital Community Health System. (26th November 2018) - Vyas, Nikunj; Hou, Cindy; Kraemer, Marianne; Condoluci, David; Cunningham, Deborah; Kim, Sungwook
Abstract: Background: Antimicrobial Stewardship Programs (ASPs) have been shown to reduce hospital-onset Clostridium difficile infection (HO-CDI) rates and antimicrobial utilization (AU). The purpose of this study was to evaluate the implementation of multidisciplinary ASP targeted toward finding a direct correlation between AU and HO-CDI. Methods: This is a 3-year review of implementation of ASP in late 2014 Q4 in three hospital health system. Multidisciplinary ASP committee was established with representation from infectious diseases, clinical pharmacy, infection control, nursing, microbiology, and informatics. Each of the three hospital implemented targeted stewardship efforts with an initial focus on monthly advanced education, daily audit and feedback for targeted antibiotics, and infectious diseases approved restricted antibiotics. We created a monthly checklist of CDC Core Elements for committee review. The primary objective of this initiative was to evaluate changes in total and targeted AU and HO-CDI within a program over a 3-year period. Subgroup analysis evaluated annual antimicrobial cost/patient day. The secondary objective was Spearman's rank correlation analysis between AU and HO-CDI. Results: Baseline overall AU analysis was based on 2014 and the intervention period included 2015, 2016, and 2017. Baseline overall AU in 2014 was 850 DOT/1, 000PD. We observed a consistent decline in overall AU in 2015, 2016, and 2017 (740, 572, and 550 DOT/1, 000PD, respectively). Targeted analysis revealed consistent decline from 2014 to 2017 in fluroquinolones (FQ) (140 vs. 35 DOT/1, 000PD) and ceftriaxone (CTX) (85 vs. 65 DOT/1, 000PD). Overall decline was also noted in rates of HO-CDI from 2014 to 2017 (5.75 vs. 3.38 per 10, 000PD). Consistent decline in overall antimicrobial cost/patient day was noted from 2014 to 2017 ($13.76 vs. $13.41/patient day). Spearman's rank correlation analysis showed positive correlation between decline in AU and HO-CDI in overall antibiotics ( r = 0.58, P = 0.022), CTX ( r = 0.61, P = 0.016), and FQ ( r = 0.54, P = 0.038). Conclusion: We present implementation of an effective health system-wide multi-disciplinary ASP. With ASP efforts over 3 years, we were able to show decline and positive correlation in overall as well as targeted AU and HO-CDI. We also noticed a consistent decline in cost/patient day in this timeframe. Disclosures: All authors: No reported disclosures.